ZDHHC9 X‐linked intellectual disability: Clinical and molecular characterization - Ramos, Anna Karolina Silva; Caldas‐Rosa, Erica Carine Campos; Ferreira, Bárbara Merfort; Versiani, Beatriz Ribeiro; Moretti, Patrícia Natalia; Oliveira, Silviene Fabiana; Pic‐Taylor, Aline; Mazzeu, Juliana F. (American journal of medical genetics. Part A, 2023)
The ZDHHC9 gene encodes the Zinc Finger DHHC‐Type Containing 9 protein that functions as a palmitoyltransferase. Variants in this gene have been reported as the cause of Raymond‐type X‐linked intellectual disability with only 16 families described in the literature. This study reviews molecular and clinical data from previously reported patients and reports the case of a 13‐year‐old patient with a splicing variant in ZDHHC9 presenting intellectual disability, developmental delay, facial dysmorphisms, and skeletal defects. Although intellectual disability and developmental delay with severe speech delay have been reported in all cases with available clinical data, the remaining clinical signs differ significantly between patients. Missense, nonsense, frameshift, and splicing variants, in addition to large exonic deletions, have been described suggesting a loss of function mechanism. Though variants are distributed in almost all exons, most missense and nonsense variants affect arginine residues located in the cytoplasmic domains of this transmembrane protein, suggesting possible mutational hotspots.